STRATEGI PEMERINTAH DAERAH DALAM PEMBERDAYAAN KELOMPOK TANI DI DESA LASIAI KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Jursang Jusrang; Andi Luhur Prianto (Department of Government Studies Universitas Muhammadiyah Makassar, 2012)
The purpose of research is to find out how the local governments in the strategy to empower the farmer in the village of Lasiai, District East Sinjai, Regency of Sinjai. This type of research is qualitative and descriptive type of research is phenomenological, with 15 informant people. Sources of data in this research is data of primary and secondary data, data collection techniques in this study is observation, interviews, documentation and FGD conducted directly by researchers. Technical analysis the data in this study is the reduction of data, serving data and verification and validation method the data in this study is a triangulation of sources, methods and triangulation time. The results showed that the local government strategy empowerment of farmers group with indicators such as using SWOT analysis is Strength, Weakness, Opportunity and Threat indicators using SWOT analysis to determine the internal and external factors in the local government to empower farmer groups so that the self-reliance of farmer groups in the village Lasiai. Tujuan penelitian adalah untuk mengetahui bagaimana strategi pemerintah daerah dalam pemberdayaan kelompok tani di Desa Lasiai, Kecamatan Sinjai Timur, Kabupaten Sinjai. Jenis penelitian adalah deskriptif kualitatif dan tipe penelitian ini adalah fenomenologis dengan informan 15 orang. sumber data dalam penelitian ini adalah data primer dan data sekunder, teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, dokumentasi dan FGD yang dilakukan secara langsung oleh peneliti teknik analisi data dalam penelitian ini adalah reduksi data, sajian data dan verifikasi dan teknik pengabsahan data dalam penelitian ini adalah triangulasi sumber, triangulasi metode dan triangulasi waktu. Hasil penelitian menunjukkan bahwa strategi pemerintah daerah dalam pemberdayaan kelompok tani dengan indikator yaitu menggunakan analisis SWOT yaitu Strenght, Weakness, Opportunity Dan Threat dengan indikator menggunakan analisis SWOT untuk mengetahui faktor internal maupun faktor eksternal pemerintah daerah dalam melakukan pemberdayaan kelompok tani sehingga terwujudnya kemandirian kelompok tani di Desa Lasiai.